Hybrids of Reduced Graphene Oxide Aerogel and CNT for Electrochemical O2 Reduction - Javier Hernández-Ferrer (MDPI AG, 2021)
Carbon nanotubes (CNTs), graphene aerogels (GAs), and their hybrid (CNT-GA) prepared by hydrothermal treatment were tested in the electrocatalytic oxygen reduction reaction (ORR). The importance of porous structure derived from the combination of mesoporosity coming from CNTs with macroporosity stemming from GAs was evidenced because the hybrid carbon material exhibited synergistic performance in terms of kinetic current and onset potential. Different electrocatalysts were prepared based on these hybrids doped with nitrogen using different precursors and also supporting Fe nanoparticles. N-doped carbon hybrids showed higher electrocatalytic activity than their undoped counterparts. Nevertheless, both doped and undoped materials provided a mixed two and four electron reduction. On the other hand, the addition of a Fe precursor and phenanthroline to the CNT-GA allowed preparing an N-doped hybrid containing Fe nanoparticles which favored the 4-electron oxygen reduction to water, thus being an excellent candidate as a structured cathode in fuel cells.